Parental perceptions of social and emotional well‐being of young children from Australian military families. - Rogers, Marg; Johnson, Amy; Coffey, Yumiko; Fielding, Jill; Harrington, Ingrid; Bhullar, Navjot (Australian Journal of Rural Health, 2023)
Introduction: Many Australian Defence Force (ADF) and Veteran families are affected by the stressors of Defence family life, including frequent and prolonged parental deployments, and frequent relocations. Objective: To address a gap in information about Defence and Veteran (hereafter Defence) parents' knowledge, confidence and resources to support their young children's well‐being and build their resilience. Design: This study used a mixed methods design to explore Defence parent's perceptions of their young children's (aged 2–8 years) social and emotional well‐being and understanding of their children's responses to unique stressors as well as their confidence in providing support. Data from 41 parents were available. Findings: Overall, parents reported positive well‐being evaluation of their children. However, just over a third of parents also reported that their children rarely cope well on two indicators combined (adapting to new situations and sharing negative emotions with others). Significantly, more than half of the parents (61%) were only partially confident in their ability to assist their children to cope with unique stressors in military families. Qualitative data provided further insights into children's struggle with relocations and parental absence and the challenges parents face in supporting them. Parents reported having limited access to effective age‐ and culturally appropriate resources to support their young children. Discussion: In a first‐of‐its kind study, we found that Australian Defence parents reported their young children were coping on most of the key well‐being indicators. However, awareness of currently available supports for children remains a barrier as well as access to contextualised, age‐ and culturally appropriate resources are lacking. Conclusion: There is a need for access to free, quality, online, research‐based Australian resources to support young children from Defence families, especially for those living in regional and rural locations and are less likely to have access to mental health and other specialist supports.